Redesigning Engineering Assessment during the Covid-19 Lockdown – A case study in Computer Networking and Network Security - Andreatos, Antonios (Technium Social Sciences Journal, 2021)
The objective of this paper is to discuss the issues that emerged during the transition from conventional face to face teaching to online teaching at the Hellenic Air Force Academy, due to the Covid-19 lockdown. A unique situation, different from both face to face lessons and distance learning, emerged: the instructors were isolated in their homes, while the students were all together in the classroom instead of being divided geographically, as happened in most conventional universities. This unprecedented situation made evaluation difficult. The paper focuses on the methods devised by the educator in order to offer personalized assignments, designed to facilitate e-assessment. As a case study, assignments and their assessment for Computer Networking II and Network Security courses are presented. Personalized assignments achieved acceptable grade statistics but were still inferior compared to face to face final exam statistics, probably because our institution was not prepared to cope with this situation. The proposed personalized assignments work best in small classes because they require manual assessment. Actions which could help universities and educators to prepare for future lockdowns (such as improving their teaching material for online teaching, enhancing student support services, etc.) are proposed. The proposed assignments could be useful to other colleagues worldwide.